On the recent occurrences of shortfin mako shark, Isurus oxyrinchus (Rafinesque, 1810) in the Adriatic Sea - Udovičić, David (Array, 2018)
Eight individuals of the shortfin mako shark, Isurus oxyrinchus (Rafinesque, 1810) have been recorded in the period from 2014 to 2017 in the Adriatic Sea. The specimens presented in the paper were identified on the basis of photographic evidence. Occurrences of juvenile specimens suggests that Adriatic Sea could serve as a nursery area for this species, especially its eastern part. A review of the previously documented occurrences of this species in the Adriatic Sea is given in this article.